KEPEMIMPINAN KEPALA SEKOLAH SEBAGAI SEORANG SUPERVISOR DALAM PENGAWASAN KINERJA GURU DI SEKOLAH DASAR - Muhammad Isnaini (El-Tsaqafah : Jurnal Jurusan PBA, 2019)
The main focus which discus in this research is how thesupervision is carried out by the principal as a supervisor. The principal’sleadership function is to carry out school management and guidancethrough administration, management and leadership activities that arehighly dependent on their abilities. The method used is a case study becauseit is to maintain the integrity of the system in a routine program. Thepurpose of this study is to determine the effectiveness of the principal’sleadership as a supervisor in supervising teacher performance. Based onthe analysis conducted concluded as follows. (1) The principal’s supervisionof teachers in primary schools has a very strategic role in determiningpolicies and improving the quality of learning processes towards achievingthe expected goals. (2) The principal is the school leader who regulates anddetermines administrative functions including the supervision function(supervision) individually or in groups, (3) In addition to the principal, theteacher also has a very decisive role in achieving the educational goals